Improving Customer Education: Study Of Customer Engagement Of Tokopedia And Shopee On Twitter Using Social Network Analysis - Rachel Anggraini Alamsyah; Tri Widarmanti (Universitas Ahmad Dahlan, 2023)
Customer education is one type of customer engagement. Through the active involvement of customers in the value creation process, customer education can give a business a competitive advantage. This study uses social network analysis (SNA) and text analysis to examine user interaction and information sharing about two Indonesian e-commerce sites on Twitter concerning customer engagement and customer education. Text data was scraped from Twitter from November 1 to December 31, 2022, and processed using Gephi and Orange software. This study found that the data shows that both official accounts of two Indonesian e-commerce become the most influential accounts in sharing information about products and services. They also play a role in educating their customers regarding the buying process, promotions, and solutions on their social networks. SNA and text analytics can be used to see customer engagement and improve customer education strategies for e-commerce to reach a competitive advantage. For further research, examining the same or different objects is recommended but using data sources from different social media, such as Instagram and Facebook.